2015
DOI: 10.4049/jimmunol.1402807
|View full text |Cite
|
Sign up to set email alerts
|

IRF5 Deficiency Ameliorates Lupus but Promotes Atherosclerosis and Metabolic Dysfunction in a Mouse Model of Lupus-Associated Atherosclerosis

Abstract: Premature atherosclerosis is a severe complication of lupus and other systemic autoimmune disorders. Gain-of-function polymorphisms in interferon regulatory factor 5 (IRF5) are associated with an increased risk of developing lupus and IRF5 deficiency in lupus mouse models ameliorates disease. However, whether IRF5 deficiency also protects against atherosclerosis development in lupus is not known. Here we addressed this question using the gld.apoE−/− mouse model. IRF5 deficiency markedly reduced lupus disease s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 81 publications
(113 reference statements)
1
41
2
Order By: Relevance
“…Taken collectively, experiments showed that the function of IRF5 is complex and may be cell‐ and stimulus‐dependent. A recent report showed that IRF5 is necessary for IL‐10 production in response to TLR7 and TLR9 stimulation in mouse GM‐CSF macrophages and DC, whereas the response to TLR2 and TLR4 ligands did not reach statistical significance, although it was lower in Irf5 −/− mice . In summary, we observed a robust activation of STAT3 and production of IL‐10 in human and mouse DC stimulated with zymosan that depends on its mannose‐based component.…”
Section: Discussioncontrasting
confidence: 49%
“…Taken collectively, experiments showed that the function of IRF5 is complex and may be cell‐ and stimulus‐dependent. A recent report showed that IRF5 is necessary for IL‐10 production in response to TLR7 and TLR9 stimulation in mouse GM‐CSF macrophages and DC, whereas the response to TLR2 and TLR4 ligands did not reach statistical significance, although it was lower in Irf5 −/− mice . In summary, we observed a robust activation of STAT3 and production of IL‐10 in human and mouse DC stimulated with zymosan that depends on its mannose‐based component.…”
Section: Discussioncontrasting
confidence: 49%
“…In lupus-prone Fasl gld/gld Apoe −/− mice, deficiency of IRF5 increased aortic root and arch lesion area and plasma levels of triglyceride, cholesterol, phospholipids, and non-esterified fatty acids, with concurrent reduction of plasma IL10 levels. Bone marrow macrophages from IRF5-deficient mice also showed reduced IL10 production in response to TLR7 ligands R848 or R837 26 . Therefore, the exact role of TLR7 in atherosclerosis remains uncertain and may depend on different experimental model systems.…”
Section: Introductionmentioning
confidence: 99%
“…For example, while IRF5 appears to be implicated in lupus pathogenesis, it appears to have a protective role in lupus-associated atherosclerosis through effects on both immune and nonimmune cells. (16)*…”
Section: Pathogenesis Of Premature Atherosclerosis In Slementioning
confidence: 99%
“…(15)* Furthermore, murine models suggest a synergism between genes that promote atherogenesis with those that promote autoimmunity, although the relationship between enhanced plaque and more profound systemic immune dysregulation requires further elucidation. (16)*…”
Section: Introductionmentioning
confidence: 99%